Formulation of refreshing non-alcoholic beverage with extracts of medicinal plants - Đorđević, Sofija M; Stanisavljević, Dragana M; Milenković, Marina T; Karabegović, Ivana T; Lazić, Miodrag L; Nikolova, Milena T; Veličković, Dragan T (Progress in Nutrition, 2019)
The paper presents the necessary analytical and technological procedures for the formulation of a new product, refreshing non-alcoholic beverage, with extracts of medicinal plants. The possibility of using ethanol-aqueous extracts of Satureja kitaibelii, Origanum vulgare, Nepeta nuda and Hyssopus officinalis for the preparation of the beverage was analysed. The base of refreshing non-alcoholic beverage was an aqueous solution with 7.0% sucrose and 0.2% citric acid. The volatile fractions of the extracts were analysed using GC-FID/GC-MS. The content of total phenols and flavonoids was determined by the spectrometric methods. Antioxidant activity was assessed by FRAP and DPPH test. Antimicrobial activity of the extracts was analysed by broth microdilution test. The extracts of O. vulgare and S. kitaibelii had the highest content of total phenols and flavonoids (129.2±12.71 and 90.0±10.56 mg GA/g DE; 110.7±2.47 and 63.3±0.58 mg RU/g DE, respectively), enhancing antioxidant activity (EC50=4.77±0.49 and EC50=18.85±0.31 µg/mL, respectively) and antimicrobial activity. Refreshing non-alcoholic beverage with Oregano extract at a concentration of 1 g/L proved to be the best combination, since it exhibited the highest antioxidant and antimicrobial activity, and sensory was the most acceptable. The formulated product had a pleasant, attractive and harmonious taste and aroma, as well as additional health benefits for consumers.